The Mediating Role of Procedural Justice on Idiosyncratic Deals and Turnover Intention Relationship - Sarp, Pınar (My University, 2018)
The main purpose of this research is to determine how much workers are affected when they make idiosyncratic deals, whether or not this situation causes turnover intention, and if the procedural justice exists as a mediating role in the relation between idiosyncratic deals and turnover intention. The study consists of two parts: theoretical and practical. First, the theoretical part is presented in order to describe the variables involved in the research, and then the research part is given. Questionnaire technique has been used as data gathering method. Rosen’s Idiosyncratic Deals Scale, Niehoff and Moorman’s Organizational Justice Scale and Hollingsworth’s Turnover Intention Scale were used as data collection tools. The obtained data were analyzed using SPSS 24.0 statistical package program. As a result of the research conducted on workers working in software and information sector in Istanbul, it has been seen that idiosyncratic deals made by workers have reduce turnover intention. As well as the fact that idiosyncratic deals has a significant effect on procedural justice, procedural justice has also a partial mediating effect on the relationship between idiosyncratic deals and turnover intention.
Keywords: Idiosyncratic Deals; Procedural Justice; Turnover Intention